A Study on the Relationship Between Learning Motivation and Learning Effectiveness of Personnel Based on Innovation Capability - Zhang, Guoqing; Chen, Chenin (Frontiers in Psychology, 2021)
Under the impact of intense competition in the face of globalization, the enhancement of the quality of human capital has become the primary goal for enterprises reinforcing the competitiveness as well as the power for constant growth and profit creation. It is the well-known norm of enterprises as well as the standard of human resource management; the enhancement of capability is the key activity of enterprises as well as the common task for modern people. Work and learning run parallel in order to cope with the rapid accumulation and change of knowledge; furthermore, in addition to enterprises providing opportunities for education, employees are requested to constantly update their training. Employees in the high-tech industry in Shanxi Province, as the research objects, were distributed 500 copies of one standard questionnaire, where 384 valid copies were retrieved, with a retrieval rate of 77%. The research results illustrate significantly positive effects of (1) learning motivation on innovation capability, (2) innovation capability on learning effectiveness, and (3) learning motivation on learning effectiveness. According to the results, providing the high-tech industry with more effective education curriculum planning and arrangement is expected.